2023
DOI: 10.1039/d2nr04680f
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric behaviour of plasma hydrogenated TiO2/cyanoethylated cellulose nanocomposites

Abstract: The interface between the polymer and nanoparticle has a vital role in determining the overall dielectric properties of a dielectric polymer nanocomposite. In this study, a novel dielectric nanocomposite containing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…18 In cyanoethylated cellulose-TiO 2 nanocomposites, the permittivities reached ε r $ 131, which was significantly higher than that of either component alone. 17 This highlights the critical role of the polymer-nanoparticle interface in determining the overall dielectric properties. In conductive polymer composites, polarization depends on electron transport between neighboring conductive fillers, known as domain-type polarization.…”
Section: Sample Labelmentioning
confidence: 95%
See 1 more Smart Citation
“…18 In cyanoethylated cellulose-TiO 2 nanocomposites, the permittivities reached ε r $ 131, which was significantly higher than that of either component alone. 17 This highlights the critical role of the polymer-nanoparticle interface in determining the overall dielectric properties. In conductive polymer composites, polarization depends on electron transport between neighboring conductive fillers, known as domain-type polarization.…”
Section: Sample Labelmentioning
confidence: 95%
“…[1][2][3][4][5][6][7][8] Dielectric permittivity is an important property of EPCs that can be used in several advanced applications, such as embedded electronics for energy storage, electromagnetic interference shielding, pulse-powered high-field electronics, and actuators. [9][10][11][12][13][14][15][16][17] Notably, the dielectric properties of certain EPCs have been reported to be markedly better than those of the parent polymer matrix, particularly in the region near the percolation threshold of the conducting filler. 18 For example, Inui et al 14 demonstrated the development of a miniaturized flexible antenna based on an EPC and established that doping with conductive silver nanoparticles increased the value more effectively than doping with BaTiO 3 nanoparticles.…”
Section: Introductionmentioning
confidence: 99%